Determination of asymptomatic endothelial dysfunction in coronary artery disease in patients with seropositive rheumatoid arthritis with asymmetric dimethylarginine (adma) and myocardial perfusion scintigraphy - Spasovski, Dejan; Sandevska, Emilija; Subeska Stratrova, Slavica (Sievert Association, 2021)
To compare the values and accuracy of the test of Asymmetric dimethylarginine (ADMA) assessed with myocardial perfusion scintigraphy (MPS), acute phase reactant, C - reactive protein (CRP) and disease activity index (DAS 28) in early diagnosis of untreated Rheumatoid arthritis (RA). To determine whether ADMA changes depend on the disease evolution. ADMA is used as an indicator for endothelial dysfunction.
Keywords: asymmetric dimethylarginine (ADMA); rheumatoid arthritis; coronary artery disease